Psycho-social factors related to willingness to use pre-exposure prophylaxis for HIV prevention among Black men who have sex with men attending a community event - Eaton, Lisa A. (Sex Health, 2014)
OBJECTIVES: In the US, Black men who have sex with men (BMSM) are disproportionately affected by HIV/AIDS. Pre-exposure prophylaxis (PrEP) holds tremendous promise for curbing the HIV/AIDS epidemic among these men. However, many psycho-social components must be addressed in order to effectively implement this prevention tool among BMSM. METHODS: We assessed PrEP knowledge and use, health care access experiences, race-based medical mistrust, sexual partners and behaviors, and drug and alcohol use among 699 men attending a community event in the southeastern US. We used generalized linear modeling to assess factors associated with their willingness to use PrEP. RESULTS: Three hundred ninety-eight men reported being BMSM and HIV negative status. Among these men, 60% reported being willing to use PrEP. Lack of being comfortable with talking to a health care provider about having sex with men, not having discussed having sex with a man with a health care provider, race-based medical mistrust, and alcohol consumption and substance use were all identified as barriers to willingness to use PrEP. Sexual risk taking, including number of sex partners and STI diagnosis, was not associated with willingness to use PrEP. CONCLUSIONS: Findings from the current paper demonstrate the importance of acknowledging the role of various psycho-social factors in the uptake of PrEP. It is imperative that we prioritize research into better understanding these barriers as the failure to do so will impede the tremendous potential of this prevention technology.